Abdominal muscle strength is related to the quality of life among older adults with lumbar osteoarthritis - Vieira, Suenimeire; Dibai-Filho Filho, Almir Vieira; Brandino, Hugo Evangelista; Ferreira, Vânia Tie Koga; Scheicher, Marcos Eduardo [UNESP] (Elsevier, 2014)
The aim of the present study was to determine the association between abdominal muscle strength and quality of life among older adults with lumbar osteoarthritis. A blind, cross-sectional study was conducted involving 40 older adults: 20 with lumbar osteoarthritis (12 women and 8 men, mean age of 65.90 ± 4.80 years) and 20 controls (14 women and 6 men, mean age of 67.90 ± 4.60 years). The volunteers were submitted to an abdominal muscle strength test. Quality of life was evaluated using the SF-36 questionnaire. Both abdominal muscle strength and quality of life scores were significantly lower in the group with lumbar osteoarthritis in comparison to the controls (p < 0.05). Moreover, significant and positive associations were found between abdominal muscle strength and the subscales of the SF-36 questionnaire (p < 0.05, 0.421 ≥ rs ≤ 0.694). Based on the present findings, older adults with lumbar osteoarthritis with greater abdominal muscle strength have a better quality of life.